The dual nature of anti-corruption agencies in China - Ma, Stephen K. (Crime, law and social change, 2008)
As the pace of modern life quickens considerably and changes come fast and furious in public affairs, the qualifications based on which public servants are recruited, the skills they are required to master in order to deal with the new situation, the challenges they are faced with, and the administrative behavior they demonstrate are all no longer the same. Bureaucrats in anti-corruption agencies are no exception. This article will review the latest development in China’s public administration, as unethical bureaucratic behavior in anti-corruption agencies has been among the increasingly vexing pathologies the authorities have to cope with.